The Important Role of Sustainable Inclusive Health System Policy in Indonesia: Lesson Learnt from the Case of Ms. H. M. in Sweden - Candrakirana, Talitha (Educationist: Journal of Educational and Cultural Studies, 2024)
People with disabilities face significant barriers to healthcare access globally, particularly in low- and middle-income countries, where only a fraction have access to necessary rehabilitation services. This paper discusses the importance of a sustainable inclusive health system policy, which integrates disability inclusion into mainstream health systems to reduce inequities. By analyzing global frameworks such as the United Nations Convention on the Rights of Persons with Disabilities and Indonesia's national legislation (Law No. 8 of 2016), the paper highlights the challenges faced by people with disabilities, including access to care during the COVID-19 pandemic. The Convention has demonstrated its efficacy through case rulings like Ms. H. M. vs. Sweden, whereas Indonesian laws have struggled to ensure equitable healthcare for disabled populations. The paper concludes by recommending improved data collection, policy reforms, and targeted research funding to better address the needs of people with disabilities in Indonesia.